The influence of thrombophilia on the long-term survival of patients with a history of venous thromboembolism - Reitter-Pfoertner, Sylvia; Waldhoer, Thomas; Mayerhofer, Michaela; Eigenbauer, Ernst; Ay, Cihan; Mannhalter, Christine; Kyrle, Paul Alexander; Pabinger, Ingrid (Thrombosis and Haemostasis, 2013)
Data on the long-term survival following venous thromboembolism (VTE) are rare,and the influence of thrombophilia has not been evaluated thus far. Our aim was to assess thrombophilia-parameters as predictors for long-term survival of patients with VTE. Overall, 1,905 outpatients (99 with antithrombin-, protein C or protein S deficiency, 517 with factor V Leiden, 381 with elevated factor VIII and 160 with elevated homocysteine levels, of these 202 had a combination and 961 had none of these risk factors) were included in the study between September 1, 1994 and December 31, 2007. Retrospective survival analysis showed that a total of 78 patients (4.1%) had died during the analysis period, among those four of definite or possible pulmonary embolism and four of bleeding. In multivariable analysis including age and sex an association with increased mortality was found for hyperhomocysteinemia (hazard ratio 2.0 [1.1.-3.5]) whereas this was not the case for all other investigated parameters. We conclude that the classical hereditary thrombophilia risk factors did not have an impact on the long-term survival of patients with a history of VTE. Thus our study supports the current concept that thrombophilia should not be a determinant for decision on long term anticoagulation. However, hyperhomocysteinaemia, known as a risk factor for recurrent VTE and arterial disease, might impact survival.
Keywords: Venous thromboembolism; thrombosis; pulmonary embolism; survival; mortality; FVIII; homocysteine